European activities on crosscutting thermal-hydraulic phenomena for innovative nuclear systems - Cheng, X.; Batta, A.; Bandini, G.; Roelofs, F.; Van Tichelen, K.; Gerschenfeld, A.; Prasser, M.; Papukchiev, A.; Hampel, U.; Ma, W.M. (Nuclear engineering and design, 2015)
•This paper serves as a guidance of the special issue.•The technical tasks and methodologies applied to achieve the objectives have been described.•Main results achieved so far are summarized. Thermal-hydraulics is recognized as a key scientific subject in the development of innovative reactor systems. In Europe, a consortium is established consisting of 24 institutions of universities, research centers and nuclear industries with the main objectives to identify and to perform research activities on important crosscutting thermal-hydraulic issues encountered in various innovative nuclear systems. For this purpose the large-scale integrated research project THINS (Thermal-Hydraulics of Innovative Nuclear Systems) is launched in the 7th Framework Programme FP7 of European Union. The main topics considered in the THINS project are (a) advanced reactor core thermal-hydraulics, (b) single phase mixed convection, (c) single phase turbulence, (d) multiphase flow, and (e) numerical code coupling and qualification. The main objectives of the project are:•Generation of a data base for the development and validation of new models and codes describing the selected crosscutting thermal-hydraulic phenomena.•Development of new physical models and modeling approaches for more accurate description of the crosscutting thermal-hydraulic phenomena.•Improvement of the numerical engineering tools for the design analysis of the innovative nuclear systems. This paper describes the technical tasks and methodologies applied to achieve the objectives. Main results achieved so far are summarized. This paper serves also as a guidance of this special issue.